Creating functional public administration : a case of Limpopo Health Department in South Africa - Modiba, N. S. (International Conference on Public Administration and Development Alternatives (IPADA), 2020)
This paper interrogates what it takes to birth a functional administration whose service delivery is consistently outlandish. The paper is conceptual and empirical in nature within the qualitative research paradigm. The question guiding this paper is: did it take other independent countries in Africa, more than 26 years to turnaround their health sectors? Narrative enquiry and interviewing techniques were used to collect data. Out of the population of 18 experienced sectional heads in the Limpopo Department of Health, South Africa, 6 were conveniently sampled. In each of the 6 sampled experienced personnel, only heads of sections became research participants. Findings revealed that lack of unity-of-purpose within the personnel, delayed the improvement of administrations. Secondly, failure, to embrace efficacy contributes to dysfunctional service delivery. Thirdly, indecisiveness is another factor. Fourthly, ignoring to reward excellence and punish mediocrity is a dilemma. Lastly, de-emphasising job-mentoring, monitoring and evaluation, is another factor. The researcher recommends for the restoration of the culture of good service and accountability by all institutional incumbents. Furthermore, health practitioners of all categories require retraining to be enabled to protect the brand 'health' against further damaging and negative stigmatisation.
Journal article published in The 5th Annual International Conference on Public Administration and Development Alternatives 07 - 09 October 2020, Virtual Conference
Keywords: Efficacy; Excellence; In-decisiveness; Mediocre; Monitoring; Public administration -- South Africa -- Limpopo; Government accountability -- South Africa -- Limpopo